Epigenetic Modification Restores Functional PR Expression in Endometrial Cancer Cells - Yang, Shujie; Xiao, Xue; Jia, Yichen; Liu, Xiaoyue; Zhang, Yuping; Wang, Xinjun; J. Winters, Christopher; J. Devor, Eric; Meng, Xiangbing; W. Thiel, Kristina; K. Leslie, Kimberly (Current Pharmaceutical Design, 2014)
Endometrial cancer, the most common gynecologic malignancy, is a hormonally-regulated tumor. Response to progestin-based therapy correlates positively with progesterone receptor (PR) expression. However, many endometrial tumors have low levels or loss of PR, limiting the clinical application of progestin. We evaluated the ability of epigenetic modulators to restore functional PR expression in Type I endometrial cancer cells with low basal PR. Treatment with the histone deacetylase inhibitor (HDACi) LBH589 induced a profound upregulation of PR mRNA. LBH589 restored PR protein expression at 24 hours and sustained expression for 72 hours, even in the presence of progesterone. LBH589 promoted a dose-dependent increase in PR protein levels, with an obvious increase with 10 nM LBH589. To investigate if the restored PR is functional as a transcription factor, we examined PR nuclear localization and expression of PRE- or Sp1-containing target genes. After treatment with LBH589 in the absence or presence of progesterone, PR nuclear expression was increased as demonstrated by Western blotting of nuclear fractions and immunostaining. Next, restored PR upregulated FoxO1, p21, and p27 and downregulated cyclin D1 in a ligand-dependent manner. Finally, LBH589 treatment induced cell cycle arrest in G1 that was further augmented by progesterone. Regulation of PR target genes was also achieved with other HDAC inhibitors, indicating that agents in this class work similarly with respect to PR. Our findings reveal that epigenetic modulators can restore endogenous functional PR expression in endometrial cancer cells and suggest that strategies to re-establish PR expression will resensitize endometrial tumors to progestin therapy.
Keywords: cell cycle arrest